ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SURAT KABAR SUARA MERDEKA PADA MASYARAKAT SEMARANG - Setiawan, Donny; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2016)
This research is motivated their sales decline can be seen from the sales data Suara Merdeka daily newspaper from 2009 to 2013 in the can from the circulation / marketing PT Suara Merdeka Press. As for the issue of research that will be developed is